Sex Differences in Demographics, Risk Factors, Presentation, and Noninvasive Testing in Stable Outpatients with Suspected Coronary Artery Disease: Insights from the PROMISE Trial - Hemal, Kshipra (JACC Cardiovasc Imaging, 2016)
OBJECTIVES: To determine whether presentation, risk assessment, testing choices, and results differ by sex in stable symptomatic outpatients with suspected coronary artery disease (CAD). BACKGROUND: Although established CAD presentations differ by sex, little is known about stable, suspected CAD. METHODS: Characteristics of 10,003 men and women in the Prospective Multicenter Imaging Study for Evaluation of Chest Pain (PROMISE) trial were compared using chi-square and Wilcoxon rank sum tests. Sex differences in test selection and predictors of test positivity were examined using logistic regression. RESULTS: Women were older (62.4 years vs. 59.0) and more likely to be hypertensive (66.6% vs. 63.2%), dyslipidemic (68.9% vs. 66.3%), and to have a family history of premature CAD (34.6% vs. 29.3) (all p-values<0.005). Women were less likely to smoke (45.6% vs. 57.0%; p<0.001), while diabetes prevalence was similar (21.8% vs. 21.0%; p=0.30). Chest pain was the primary symptom in 73.2% of women vs. 72.3% of men (p=0.30) and was characterized as “crushing/pressure/squeezing/tightness” in 52.5% of women vs. 46.2% of men (p<0.001). Compared to men, all risk scores characterized women as lower risk, and providers were more likely to characterize women as having low (<30%) pre-test probability for CAD (40.7% vs. 34.1%; p<0.001). Compared with men, women were more often referred to imaging tests (adjusted OR 1.21; 95% CI 1.01–1.44) than non-imaging tests. Women were less likely to have a positive test (9.7% vs. 15.1%; p<0.001). Although univariate predictors of test positivity were similar, in multivariable models, age, BMI, and Framingham risk score were predictive of a positive test in women, while Framingham and Diamond and Forrester risk scores were predictive in men. CONCLUSION: Patient sex influences the entire diagnostic pathway for possible CAD, from baseline risk factors and presentation to noninvasive test outcomes. These differences highlight the need for sex-specific approaches to CAD evaluation.